Postoperative nursing of integrated traditional Chinese and Western medicine for an elderly patient undergoing surgery for thyroid cancer (1例老年甲状腺癌患者术后中西医结合护理体会) - SHI Yu (石宇); LI Yueru (李月茹); SHANG Cui (商翠); CAO Hongjing (曹红京); LI Ning (李宁); LI Jing (李静) (Association of Integrative Nursing, 2024)
This article summarized the postoperative nursing of integrated traditional Chinese and Western medicine for an elderly patient undergoing surgery for thyroid cancer. Comprehensive nursing interventions such as basic nursing, acupuncture massage, dietary nursing, exercise guidance and psychological care were carried out. A comprehensive nursing plan of integrated traditional Chinese and Western medicine had been made to relieve the negative emotion and pain of the patient, and improve the sleep quality and quality of life during rehabilitation. (本文总结1例老年甲状腺癌患者术后中西医结合护理经验。根据患者术后症状, 完善基础护理, 中西医联合用药, 并采用针灸按摩、饮食调护、运动指导、心理干预等护理方法, 内外结合, 提升患者治疗信心, 缓解其负性情绪, 减轻疼痛, 改善睡眠质量, 提高患者的生活质量。)